FEDERALISM AND THE ADJUDICATION OF CONSTITUTIONAL ISSUES: THE ETHIOPIAN EXPERIENCE - Fiseha, A. (Netherlands international law review, 2005)
Since 1995, Ethiopia has embarked upon a new federal system. Very little has been written about the process in general and about the manner in which the issues concerning the division of powers between the federal government and the states in Ethiopia are adjudicated The federal Constitution has several peculiar features. One of these relates to the institution empowered to interpret and adjudicate constitutional issues. Unless there is a tribunal that enforces the supremacy clause of the Constitution and that demarcates the proper sphere of the powers of the federal and state governments, chaos would result from jurisdictional conflicts. This power, by virtue of the federal Constitution belongs to the second chamber, otherwise known as the House of Federation. This article begins with a brief introduction of the federal system and proceeds to discuss the role, jurisdiction and procedure of the House of Federation (HOF) in the adjudication and interpretation of constitutional issues from a comparative perspective. It explains why vesting this power on the HOF, and not on the judiciary, was a policy choice.